A new gecko of the genus Tarentola (Squamata: Gekkonidae) from Eastern Cuba - Díaz, Luis M.; Hedges, S. Blair (Zootaxa, 2008)
A new, diminutive, and cryptic species of the genus Tarentola (T. crombiei sp. n.) is described from the arid south coast of Granma, Santiago de Cuba, and Guantánamo provinces in eastern Cuba. Specimens of this species have been in collections for nearly 100 years but its close resemblance to sympatric Tarentola americana delayed its detection. It differs from that species in body size, scalation, clutch size, and molecular phylogeny.